Risk factors for peripartum hysterectomy following uterine rupture. (14th March 2013) - Charach, Ron; Sheiner, Eyal
Abstract: Objective : To investigate risk factors for hysterectomy following uterine rupture. Methods : A population-based study comparing all uterine ruptures with and without hysterectomy between 1988 and 2011 was conducted. Stratified analysis was performed using a multiple logistic regression analysis. Results : Peripartum hysterectomy complicated 20.7% ( n = 34) of uterine ruptures during the study period ( n = 164). Independent risk factors for hysterectomy following uterine rupture, from a multivariable logistic regression model, were relaparotomy (OR = 32.2, 95% CI = 2.5–421.9), extended tears involving the uterine cervix (OR = 6.1, 95% CI = 1.5–24.7), severe bleeding requiring packed cells transfusions (OR = 13.7, 95% CI = 3.2–58.5) and grand multiparity (≥5 deliveries, OR = 11.4 95% CI = 2.7–47.1). Conclusion : Hysterectomy is not common following uterine rupture. Independent risk factors for hysterectomy include relaparotomy, extended tears involving the uterine cervix, severe bleeding requiring packed cells transfusions and grand multiparity. Trained obstetricians should be involved in cases of uterine rupture and the possibility for conducting hysterectomy should be emphasized.